The synthesis and reactivity of cationic terminal borylene complexes - Pierce, G; Glesni Angharad Piercece (2010)
This thesis describes the synthesis, structure/bonding studies and reactivity of cationic terminal borylene complexes. Reactions of the cationic terminal borylene complexes, [CpFe(CO)₂(BNR₂)]⁺[BArf₄]⁻ (R = Cy, ⁱPr) with heteroallenes have been investigated and shown to proceed by initial coordination of the substrate at the electrophilic boron centre. Reaction with isocyanate ultimately forms [CpFe(CO)₂(CNPh)]⁺[BArf₄]⁻ by a net metathesis process. Dicyclohexylcarbodiimide, however, reacts by insertion into the Fe=B bond of the aminoborylene to form [CpFe(CO)₂C(NCy)₂BNR₂]⁺[BArf₄]⁻. An excess of the substrate yields the spirocyclic complex, [CpFe(CO)₂C(NCy)₂B(NCy)₂BNR₂]⁺[BArf₄]⁻ via a second insertion into the B=N bond. Computational studies investigating insertion and metathesis reaction pathways of these aminoborylene complexes are also reported. Reactions of dicyclohexylcarbodiimide with three-coordinate aminoborane and aminoboryl complexes are described. Formation of the first boron guanidinate complexes featuring dihalide substituents, Cy₂NC(NCy)₂BCl₂ and ⁱPr₂NC(NCy)₂BCl₂ by both salt metathesis and carbodiimide insertion routes are reported. The aminoboryl complexes, CpFe(CO)₂B(NPh₂)Cl and CpFe(CO)₂B(NBz₂)Cl have also been synthesized and their reactions with carbodiimides probed. A novel cationic terminal borylene complex, [Cp'Fe(CO)₂(BNⁱPr₂)]⁺ [BArf₄]⁻ featuring a methyl-substituted Cp ring is reported and represents the first structurally characterized isopropyl substituted aminoborylene complex. Substitution of the ancillary carbonyl ligands of cationic terminal borylene complexes has been investigated. Irradiation of the aminoboryl precursor complex, CpFe(CO)₂B(NCy₂)Cl in the presence of trialkylphosphines, PR₃ (PR₃ = PMe₃, PPh₃, P(OMe)₃) yield the mono(phosphine) complexes, CpFe(CO)(PR₃)B(NCy₂)Cl. The mono(substituted) dimer [{CpFe(CO)(BNCy₂)}₂(μ-dmpe)] was also formed from the reaction with the chelating ligand, dmpe. Replacement of the second carbonyl is prevented by the steric bulk of the dicyclohexylamino substituent, and instead [CpFe(CO)(PR₃)₂]⁺Cl⁻ is formed by extrusion of the borylene fragment. The mono(phosphine) ligated cationic terminal borylene complexes, [CpFe(CO)(PR₃)(BNCy₂)]⁺[BArf₄]⁻ were subsequently formed by halide abstraction. Both [CpFe(CO)(PMe₃)(BNCy)₂]⁺[BArf₄]⁻ and the bridging dication [{CpFe(CO)(BNCy₂)}₂(μ-dmpe)]₂⁺[BArf₄]⁻₂ were structurally authenticated. Replacing the bulky cyclohexyl groups of the aminoboryl precursor for methyl groups allowed synthesis of the bis(substituted) complexes, CpFe(PMe₃)₂B(NMe₂)Cl and CpFe(dmpe)B(NMe₂)Cl. Extraction of these complexes into dichloromethane resulted in formation of the borylene, [CpFe(PMe₃)₂(BNMe₂)]⁺Cl⁻ and [CpFe(dmpe)(BNMe₂)]⁺Cl⁻ by spontaneous halide ejection.